2017
DOI: 10.1242/jeb.149682
|View full text |Cite
|
Sign up to set email alerts
|

Self-fertilization, sex allocation and spermatogenesis kinetics in the hypodermically-inseminating flatworm Macrostomum pusillum

Abstract: The free-living flatworm genus Macrostomum is an emerging model system for studying the links between sex allocation, sexual selection and mating system evolution, as well as the underlying developmental and physiological mechanisms responsible for wide intra-and inter-specific variability in reproductive phenotypes. Despite compelling comparative morphological evidence of sexual diversity, detailed experimental work on reproductive behaviour and physiology in Macrostomum has so far been largely limited to jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 69 publications
2
29
0
1
Order By: Relevance
“…In contrast, the reciprocal mating syndrome involves reciprocal copulation (e.g., M. lignano , see Schärer, Joss, & Sandner, ), during which both partners reciprocally transfer sperm into the female antrum (sperm receiving organ) of the partner. Both earlier reports of self‐fertilization in Macrostomum are in species that are hypodermically inseminating (e.g., M. hystrix , see Ramm, Vizoso, & Schärer, ; Ramm, Schlatter, Poirier, & Schärer, ; and M. pusillum , Giannakara & Ramm, ), with both species showing a similar needle‐like stylet morphology that potentially facilitates self‐fertilization by allowing self‐injection of sperm. In contrast, the current study documents the first occurrence of self‐fertilization in a reciprocally copulating species, M. mirumnovem , which has a large blunt‐ending stylet (Schärer et al, ), and for which we currently do not understand how selfing is actually achieved.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In contrast, the reciprocal mating syndrome involves reciprocal copulation (e.g., M. lignano , see Schärer, Joss, & Sandner, ), during which both partners reciprocally transfer sperm into the female antrum (sperm receiving organ) of the partner. Both earlier reports of self‐fertilization in Macrostomum are in species that are hypodermically inseminating (e.g., M. hystrix , see Ramm, Vizoso, & Schärer, ; Ramm, Schlatter, Poirier, & Schärer, ; and M. pusillum , Giannakara & Ramm, ), with both species showing a similar needle‐like stylet morphology that potentially facilitates self‐fertilization by allowing self‐injection of sperm. In contrast, the current study documents the first occurrence of self‐fertilization in a reciprocally copulating species, M. mirumnovem , which has a large blunt‐ending stylet (Schärer et al, ), and for which we currently do not understand how selfing is actually achieved.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, an earlier study in M. pusillum-a species that regularly self-fertilizes-has shown that the species does not exhibit any plasticity in SA in response to group size (Giannakara & Ramm, 2017). In contrast, M. hystrix-a facultatively self-fertilizing species-does adjust its SA depending on group size (Winkler & Ramm, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations